1986
DOI: 10.1111/j.1600-0609.1986.tb02326.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma lactoferrin content: Differential effect of steroid administration and infective illnesses: Lack of effect of ambient temperature at which specimens are collected

Abstract: The effect of parenteral hydrocortisone on plasma lactoferrin concentration, neutrophil count and 1actoferrin:neutrophil ratio was assessed in 10 volunteer subjects.Administration of a single dose of corticosteroid was followed by a significant rise in the circulating neutrophil count, a significant but proportionately smaller rise in the plasma lactoferrin concentration and a significant fall in the 1actoferrin:neutrophil ratio. Acute viral infections were found to be associated with a disproportionately low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Epithelial cells in the mucosa of many mammalian species produce Lf and, as a result, this protein is present in numerous mucosal secretions such as tears, saliva, seminal and vaginal fluids and plasma [39,42]. Furthermore, Lf is present in secondary granules of neutrophilic granulocytes, where it is stored until cellular activation [43]. Lf is considered an important component of the non-specific immune system since the protein is strategically situated in the first line of defense against microbial infections [40].…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells in the mucosa of many mammalian species produce Lf and, as a result, this protein is present in numerous mucosal secretions such as tears, saliva, seminal and vaginal fluids and plasma [39,42]. Furthermore, Lf is present in secondary granules of neutrophilic granulocytes, where it is stored until cellular activation [43]. Lf is considered an important component of the non-specific immune system since the protein is strategically situated in the first line of defense against microbial infections [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, all these amounts are comparable to those reported for other species. Human neutrophil lactoferrin content has been variously reported as 4.3 lg per 10 6 cells (Venge et al, 1978), 3.0 lg per 10 6 cells (Masson et al, 1969), and 8.2 lg per 10 6 cells (Baynes et al, 1986), while a figure of from 2 to 4 lg per 10 6 cells has been reported for mouse neutrophils (Segars and Kinkade, 1977). Based on this sampling of data, it is reasonable to assume 8.0 lg lactoferrin per 10 6 bovine neutrophils, as a basis for further calculations.…”
Section: Neutrophil Lactoferrin Contentmentioning
confidence: 99%
“…8 Our data confirm an earlier study that showed administration of corticosteroids to normal volunteers increased lactotransferrin protein levels in blood. 9 Lipocalin 2 is important in removing or preventing iron from entering siderophore bound iron in bacteria. 10 Lipocalin 2 also binds and carries iron in neutrophils, 11 and plays a role in resistance against tissue injury.…”
Section: Dmd-steroid Vs Dmdmentioning
confidence: 99%